Overweight and obesity in women in Burkina Faso: Socio-cultural and behavioural factors - Bernard dembele Dembele (World Nutrition)
Overweight, obesity, and associated non-communicable diseases are global public health issues. Initially confined to developed nations, they are now spreading to least developed countries as a result of the globalisation of dietary attitudes and practices, which have greatly increased the consumption of ultra-processed and other obesogenic products. In developing countries, women are more likely to be overweight or obese than men. Burkina Faso is not an exception in this pattern. It is the reason why this analysis was initiated to highlight the socio-cultural and behavioural factors underlying this phenomenon among women. It aims at emphasizing the prominent characteristics of overweight/obese women to help formulate accurate actions and interventions. To this end, the data used come from the Burkina Faso 2021 Demographic and Health Survey, which covered a nationally representative sub-sample of 8,852 women aged 15-49 years, on whom anthropometric measurements (height and weight) were collected. The analyses revealed that overweight and obesity affect at least one in five women, and are linked predominantly to the possession of rapid means of transportation, practice of sedentary activities, having a high living standard, consumption of dietary diversity, having a high level of education, older age, frequent consumption of sweetened beverages, connected to internet, urban residence, membership in certain ethnicities and multi-parity. This highlights the multidimensional nature of overweight and obesity and the need for multi-faceted actions to control the current upward trend. Priority should be given to balanced diets low in ultra-processed foods, daily physical exercise, and their influencing parameters.